The Influence Of Discounts And Free Shipping On Interest In Buying At Shopee - Artanti Arubusman, Dian (Yayasan Pendidikan Belajar Berdikari, 2024)
Shopee has grown to play a significant role in the lives of customers due to the industry's explosive growth. The purpose of this study is to learn how consumers perceive the elements in the Shopee ecosystem that influence purchases. The purpose of this study is to ascertain how two primary elements—discounts and free shipping—affect consumers' propensity to purchase from the Shopee. This study method is qualitative in nature and involves a quick discussion, a review of the literature, and each component influencing a purchase choice. The study's findings paint a comprehensive picture of how crucial sales and free delivery are to Shopee customers' desire to make a purchase.